Peningkatan Keterampilan Anak Buah Kapal Dalam Keselamatan Pelayaran di Kapal KM. Thalia - Rahman Raising; Rusnaedi; Ratnawati Raising; Sudarman (Politeknik bumi Akpelni, 2026)
Maritime safety on passenger ships is highly dependent on the readiness and skills of crew members (ABK) in implementing procedures, communicating effectively, and responding to emergencies quickly and correctly. This study aims to analyze the crew’s initial skill levels, identify factors contributing to ineffective safety drills, and formulate strategies to improve safety-related skills on KM. Thalia. A qualitative descriptive case-study method was employed through direct observation, interviews/communication with key informants, and document and maritime-safety literature review. The findings indicate a gap between expected procedures and actual practice during fire drills: the crew’s initial response was slow, muster time at the muster station exceeded the 5-minute target, understanding of assigned duties based on the muster list was uneven, and technical proficiency in using fireman outfits and breathing apparatus was inconsistent within the required drill timeframe. Key contributing factors include irregular drills, limited voyage time and weather constraints, suboptimal leadership motivation and supervision, varied crew experience levels, and inadequate maintenance of firefighting equipment. The study concludes that improving crew skills is most effectively achieved by strengthening both the frequency and quality of scheduled drills, supported by active safety leadership to build discipline, communication, and a safety culture onboard.